Determining factors for destination university selection at the international arena - García Waldman, David Horacio; Tamez González, Gerardo; Leyva Cordero, Oswaldo (Universidad del Zulia, 2018)
This article analyzes the factors that influence the decision of international students to select the destination university. These decisions are examined in two categories, endogenous and exogenous factors, which are decisive for selecting the destination university. In this sense, the research is approached from a quantitative approach. Among the most relevant factors found, professional development is observed, which implies improving employment opportunities as a key element, in addition to the educational quality of the Institution, focused on the reputation of the university, the educational program, the relevance of the program and quality of teachers.